2005
DOI: 10.1111/j.1600-051x.2005.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Healing of intra‐bony defects following treatment with a composite bovine‐derived xenograft (Bio‐Oss Collagen) in combination with a collagen membrane (Bio‐Gide PERIO)

Abstract: Within the limits of the present study, it can be concluded that the combination of BDX Coll+GTR resulted in significantly higher CAL gains than treatment with access flap surgery alone, and thus appears to be a suitable alternative for treating intra-bony periodontal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 21 publications
5
56
2
1
Order By: Relevance
“…These grafting materials are also referred to as natural bone minerals, since proprietary processes are suggested to remove all cells and proteinaceous material, leaving behind an inert bone scaffold exhibiting a specific three-dimensional surface structure 42 . Recently, a natural bone mineral was coated with porcine derived collagen to render its surface even more attractive for cell adhesion (GBO, BioOss Collagen 1 ) 35,40 . Amongst the alloplastic materials, HA and tricalcium phosphate (TCP) were most commonly used for bone regeneration in combination with GBR and well accepted due to lack of possible disease transmission 5,16 .…”
mentioning
confidence: 99%
“…These grafting materials are also referred to as natural bone minerals, since proprietary processes are suggested to remove all cells and proteinaceous material, leaving behind an inert bone scaffold exhibiting a specific three-dimensional surface structure 42 . Recently, a natural bone mineral was coated with porcine derived collagen to render its surface even more attractive for cell adhesion (GBO, BioOss Collagen 1 ) 35,40 . Amongst the alloplastic materials, HA and tricalcium phosphate (TCP) were most commonly used for bone regeneration in combination with GBR and well accepted due to lack of possible disease transmission 5,16 .…”
mentioning
confidence: 99%
“…Moreover, the osseointegration period was confirmed to range between 9 and 18 months. On the other hand, bovine bone matrix showed, in the same conditions, a longer resorption time, even with controversial histomorphometrical outcomes (28). At the end of this study, the reported outcomes showed a strong bone regeneration, with a bone regeneration mean value of 7.85±1.9 mm.…”
Section: Discussionmentioning
confidence: 49%
“…Collagen maintains inorganic particles and blood clots, and has excellent formability, which allows it to be shaped to fit defects. These properties and other make collagen the most useful material for preparing composite materials [18,48]; furthermore, its safety has been well proven in clinical practice. However, no material has ideal properties for bone grafts, and, thus, efforts to identify better new materials are ongoing.…”
Section: Discussionmentioning
confidence: 99%